2020
DOI: 10.1021/acsaem.0c02487
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering in Crystalline Cobalt Tungstate/Amorphous Cobalt Boride Heterogeneous Nanostructures for Enhanced Electrochemical Performances

Abstract: Interfacial engineering is one of the feasible pathways to tune the characteristics and functions of nanomaterials. In this report, we successfully synthesized crystalline CoWO 4 /amorphous Co−B heterostructures that enable superior electrochemical performance. The electrodes overcome the defect of low conductivity of cobalt tungstate and also expose more active sites. The optimized CoWO 4 /Co−B electrode has a remarkable specific capacity of 177.4 C g −1 at 0.5 A g −1 and a great specific capacity retention o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…12(c), the C s for CoWO 4 electrode film prepared by the CP method are 160.5, 173.9, 188.4, As can be presented in Table 6 above, we have noted some well significant differences in C s values for pure CoWO 4 crystals and modified CoWO 4 crystals when compared with other previous papers reported in the literature [26,39,40,43,51,52, 53,54,135,13 7-147] of the crystalline and amorphous state. These differences at minor C s values that have already been previously reported in the literature [43,51,52,138,143,145,146,147] about our CoWO 4 crystals can be possibly ascribed to the relatively slower redox rates on the cobalt actives sites, cobalt deficiencies or oxygen vacancies. Moreover, based on our previous experimental and theoretical analysis is noted the presence of the effect of order-disorder at the monoclinic lattice through Rietveld refinement data at the long-range, non-homogeneous distribution of electronic charges on surfaces mainly for CoWO 4 nanocrystals prepared by the CP method, Raman-active vibrational modes are not wellsharp or defined at Raman spectra at short-range, distortions in the between (O-W-O) and (O-Co-O) bonds found in FT-IR spectra.…”
Section: Supercapacitor Propertiessupporting
confidence: 71%
“…12(c), the C s for CoWO 4 electrode film prepared by the CP method are 160.5, 173.9, 188.4, As can be presented in Table 6 above, we have noted some well significant differences in C s values for pure CoWO 4 crystals and modified CoWO 4 crystals when compared with other previous papers reported in the literature [26,39,40,43,51,52, 53,54,135,13 7-147] of the crystalline and amorphous state. These differences at minor C s values that have already been previously reported in the literature [43,51,52,138,143,145,146,147] about our CoWO 4 crystals can be possibly ascribed to the relatively slower redox rates on the cobalt actives sites, cobalt deficiencies or oxygen vacancies. Moreover, based on our previous experimental and theoretical analysis is noted the presence of the effect of order-disorder at the monoclinic lattice through Rietveld refinement data at the long-range, non-homogeneous distribution of electronic charges on surfaces mainly for CoWO 4 nanocrystals prepared by the CP method, Raman-active vibrational modes are not wellsharp or defined at Raman spectra at short-range, distortions in the between (O-W-O) and (O-Co-O) bonds found in FT-IR spectra.…”
Section: Supercapacitor Propertiessupporting
confidence: 71%
“…[109] Hou et al demonstrated the enhanced supercapacitor performance on the crystalline-amorphous CoWO 4 /Co-B heterostructures because of the improved conductivity and exposed more active sites. [171] As schematically illustrated in Figure 6a, Jiang et al proposed a two-step hydrothermal approach to prepare amorphouscrystalline MoO 3 -Ni 3 S 2 /NF 0.5 nanosheet arrays with abundant heterointerfaces as the battery-type electrodes for supercapacitor. [172] The crystalline Ni 3 S 2 components are designed to get enormous structural nanocrystallization and improve the efficiency of redox reaction.…”
Section: Supercapacitormentioning
confidence: 99%
“…demonstrated the enhanced supercapacitor performance on the crystalline‐amorphous CoWO 4 /Co‐B heterostructures because of the improved conductivity and exposed more active sites. [ 171 ]…”
Section: Electrochemical Performance Of Amorphous‐crystalline Heteros...mentioning
confidence: 99%
“…By now, plenty of research studies have reported that alkaline batteries exhibit relatively low specific capacity and poor cycling stability, which is ascribed to the low conductivity and unstable structure of nickel-based oxide and hydroxide cathode materials, such as Ni­(OH) 2 and NiO. , Numerous studies have been carried out to improve the intrinsic conductivity of nickel-based cathodes, such as sulfides, selenides, and phosphides, even conductive organic ligand incorporation. Nowadays, nickel-based borides have become popular because of their relatively high conductivity and environmentally friendly nature; however, research studies have mainly focused on electrocatalytic water splitting. As alternative to noble metal electrocatalysts, nickel-based borides exhibit long-term durability in an alkaline medium, which has aroused researchers’ interest in the development of alkaline battery energy storage. ,, The semiconductive property of nickel-based borides prompts electron transfer easily, resulting in fast kinetics during the electrochemical reaction. For the intercalation-type battery material, intrinsic conductivity and electrolyte ion-shuttling diffusion are the two most important factors that have a great effect on the reaction kinetics of active materials. In our previous report, the naphthalene dicarboxylate acid ligand pillared a Ni/Co layer in the NiCo metal–organic framework (MOF) to form ion intercalation/de-intercalation channels. This verified that the ion-shuttling channel enlarged linearly with the larger pillaring layer space. ,, However, more organic ligands introduced would render low conductivity, leading to slow chemical reaction kinetics. , …”
Section: Introductionmentioning
confidence: 99%